Subsidized news-media innovation: outputs, outcomes, and impact - Kammer, Aske; Blach-Ørsten, Mark (Frontiers in Communication, 2025)
Digital disruptions have put an emphasis on innovation as a means for survival for news and journalism in uncertain times. As a response, Denmark introduced a targeted subsidy instrument for news-media innovation in 2014 to support both the establishment of new news media and the development of legacy media. This study analyzes the first decade of this subsidy instrument (2014–2023), where a total of 23,573,219 EUR was allocated. Guided by studies based on innovation-policy impact assessment, we map and evaluate the news-media innovation subsides with a focus on outputs, outcomes, and impact. The analysis shows that 52 % of the subsidies has been allocated to legacy media, the rest to new news media. Furthermore, we find that new news media predominantly do innovation aimed at content and market development, whereas legacy media pursue product development. One outcome is that 44 new news media have been established with the support of the subsidy instrument, 31 of which still exist. Finally, in terms of impact, the analysis shows that of the 31 new news media, only few are both widely recognized and used by the Danish population.